SEGUIMIENTO Y CONTROL DE BIODETERIORO MICROBIOLÓGICO EN DOCUMENTOS DE INTERÉS HISTÓRICO EN EL ARCHIVO GENERAL DE LA NACIÓN (2004)
Starting from the support papers (manual, bond and newspapers ), photography with gelatin and silver emulsion and planes with support in  textile fiber of Colombia’s General Archive, different isolation tests and identification of fungi were carried out to determine the stains with highest appearance frequencies and the effect of the disinfectant Tego51®,  Timsen® to 4000 ppm (1.6 g of n-alquil dimetil bencil), Ethanol to 70% and Newger® to 0.7% (N-Duopropenida).Equally at 231, photography with gelatin emulsion of the bottom of the Ministry of Public works (MOP) that presented biodeterioration  indicators, we) carried out isolation and identification of 48 fungal stains, and found two fungal stains with the highest appearance frequencies,  Penicillum sp and Cladosporium sp, and the two with the highest levels of aggression to the applied supporting substances, Rhizopus sp,  Cladosporium sp, Aspergillus sp 1 and Fusarium sp, with   biodeterioration effect in 25b days.At the beginning, Penicillum sp, Cladosporium sp, Rhizopus sp and Aspergillus sp 1 were selected for evaluating three disinfectants at  three  different concentration levels (Timsen® to 1000 ppm, 2000 ppm and 3000 ppm, Ethanol to 50%, 70% and 80% and Newger® to 0.5%, 0.7% and 1%) to determine the fungicidal effect and their action on the photographic support.Finally, 66 planes with support in textile fiber were also evaluated starting with the ones which were isolated and 37 fungal stains were  identified. The two fungal stains with the highest appearance frequencies were Penicillum sp and Cladosporium sp which also demostrated high  aggressiveness in the support together as well as Bipolaris sp.